Karst vegetation in the natural habitat of sandalwood (Santalum album) at various altitude places in Timor Island, Indonesia - FRANSISCA XAVERIANA SERAFINA LIO; MARIA PAULIN SARI DEWI (Biodiversitas Journal of Biological Diversity, 2018)
Lio FXS, Dewi MPS. 2018. Karst vegetation in the natural habitat of sandalwood (Santalum album) at various altitude places in Timor Island, Indonesia. Biodiversitas 19: 1703-1713. Sandalwood (Santalum album L.) was the superior commodity In South Central Timor District, but it tends to decrease in number at present. South Central Timor has been highly regarded for the quality and former abundance of its sandalwood stocks and it has been one of the most productive sources for sandalwood on Timor Island. It grows in the karst ecosystem at altitude of 450-1044 m asl. This study aims to assess karst vegetation in the natural habitat of sandalwood at three elevation sites in South Central Timor. A total of 4 plots were placed in the middle land zone (307-382 m asl.), 7 plots in the upland zone (784-1031 m asl.), and 4 plots in the highland zone (1665-1782 m asl.). Data were sampled using a square plot measuring 20 x 20m for tree, and the sub-plot of 1 x 1m for the ground vegetation category. Ecological data were measured together with the sampling of vegetation data, while the soil quality was assessed in the laboratory of Nusa Cendana University. The results showed that the higher a place from the sea surface, the less number of species was found. The highest number of species was found in the upland zone, but it tended to decrease in the highland zone. Dominant species placed at each zone were also different, which in the middeland zone the dominant species were Acacia mangium, Tectona grandis, and Eleusine indica; in the upland zone, they were Lantana camara, Gmelina arborea, Senna siamea and Cyperus rotundus, whereas in highland zone was dominated by Senna occidentalis, Portulaca oleracea, Eucalyptus urophylla, and C. rotundus. The results of multiple regression analysis also showed that environmental factors did not affect the species number in research sites. Ecological condition and soil quality in research sites indicated that those conditions are suitable for sandalwood's growth.